Heat Transfer in Magnetohydrodynamic Flow of a Casson Fluid with Porous Medium and Newtonian Heating - Hussanan, Abid; Mohd Zuki, Salleh; Khan, Ilyas; Razman, Mat Tahar (American Scientific Publishers, 2017)
This paper deals with exact solutions for unsteady magnetohydrodynamic (MHD) flow of a Casson fluid over an infinite vertical oscillating plate embedded in a porous medium. The analysis of heat transfer in the presence of Newtonian heating is also considered. Some suitable non-dimensional variables are introduced. The governing equations together with imposed conditions are transformed into dimensionless forms. Expressions for the velocity and temperature fields are obtained using the Laplace transform. Skin-friction and Nusselt number are also evaluated. Solution for Newtonian fluid is also reduced as a special case. The graphical results show that velocity decreases significantly with increases of magnetic effects, but it increases when either conjugate parameter or porosity parameter increases. The main outcomes of the present work is that fluid flow can be controlled by the increasing the values of Prandtl number as well as by the increasing of Casson parameter.